The Effect of Competence, Training, Compensation on Job Satisfaction and Employee Performance - Adi Kurnia; Ari Ramdani (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2021)
This research was conducted at the Department of Transportation of the City of Tasikmalaya. The selection of the object of this research is based on the existence of several problems. The first problem relates to training, and the second problem relates to compensation, which is suspected to have an effect on job satisfaction and employee performance. This study aims to determine, analyze and interpret the relationship between the direct and indirect effects of competence, training, compensation on job satisfaction and employee performance at the Department of Transportation of the City of Tasikmalaya. The research method used is a descriptive-correlation method with a quantitative approach with testing on 30 samples of respondents taken through an expert formula from Gay and Diehl in (Indrawan & Poppy, 2017) with 25% of the population of employees at the Department of Transportation of the City of Tasikmalaya. Based on the results of the study, it was found that Competence, Training, Compensation through Satisfaction simultaneously affected the Performance of the Tasikmalaya City Transportation Service Employees. worth 91.3% and others 8.7% caused by other variables that were not examined